Changes in Methylation Patterns of Kiss1 and Kiss1r Gene Promoters across Puberty. (January 2013) - Wyatt, Amanda K.; Zavodna, Monika; Viljoen, Jean L.; Stanton, Jo-Ann L.; Gemmell, Neil J.; Jasoni, Christine L.
The initiation of mammalian puberty is underpinned by an increase in Kisspeptin (Kiss1) signaling via its receptor (Kiss1r/GPR54) on gonadotropin-releasing hormone (GnRH) neurons. Animals and humans with loss-of-function mutations in Kiss1 or Kiss1r fail to go through puberty. The timing of puberty is dependent on environmental factors, and malleability in puberty timing suggests a mechanism that can translate environmental signals into patterns of Kiss1/Kiss1r gene expression. Epigenetics is a powerful mechanism that can control gene expression in an environment-dependent manner. We investigated whether epigenetic DNA methylation is associated with gene expression changes at puberty. We used bisulfite-PCR-pyrosequencing to define the methylation in the promoters of Kiss1 and Kiss1r before and after puberty in female rats. Both Kiss1 and Kiss1r showed highly significant puberty-specific differential promoter methylation patterns. By identifying key differentially methylated residues associated with puberty, these findings will be important for further studies investigating the control of gene expression across the pubertal transition.